2019
DOI: 10.1515/geo-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric refractivity estimation from AIS signal power using the quantum-behaved particle swarm optimization algorithm

Abstract: This paper proposes a new refractivity profile estimation method based on the use of AIS signal power and quantum-behaved particle swarm optimization (QPSO) algorithm to solve the inverse problem. Automatic identification system (AIS) is a maritime navigation safety communication system that operates in the very high frequency mobile band and was developed primarily for collision avoidance. Since AIS is a one-way communication system which does not need to consider the target echo signal, it can estimate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…e expected evaluation effect cannot motivate the team of counselors to actively tap their own potential and create higher performance [10]. And because the counselor's own work has not received a comprehensive and accurate response, it will dampen their enthusiasm for work to a certain extent [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e expected evaluation effect cannot motivate the team of counselors to actively tap their own potential and create higher performance [10]. And because the counselor's own work has not received a comprehensive and accurate response, it will dampen their enthusiasm for work to a certain extent [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among them, passive wireless SAW sensors have high sensitivity and good stability and have gained wide attention and research. SAW sensors are a relatively new branch of application of SAW devices [4], using SAW resonators as sensing units. When a passive SAW wireless sensor performs detection, a fork-finger transducer converts the electromagnetic signal received by the sensor antenna into a sound surface wave.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the problem, Tang et al proposed an estimation method of refractive index distribution based on the automatic recognition system and quantum behavior particle swarm optimization. The simulation analysis of this method showed that it could accurately retrieve the surface air duct and accurately estimate the atmospheric refractive index [10].…”
Section: Related Workmentioning
confidence: 99%
“…Num max represents the maximum number of crossings. Individual P i can be expressed in the form of real number matrix, as shown in formula (10) [26], [27], [28].…”
Section: Optimization Based On Improved Psomentioning
confidence: 99%
See 1 more Smart Citation